Mechanism of angiogenesis promotion with Shexiang Baoxin Pills by regulating function and signaling pathway of endothelial cells through macrophages. (January 2020) - Zhang, Jiange; Cui, Qianfei; Zhao, Yiran; Guo, Runan; Zhan, Changsen; Jiang, Peng; Luan, Pengwei; Zhang, Pei; Wang, Feiyun; Yang, Liuqing; Yang, Xiyan; Xu, Yulan
Abstract: Background and aims: "Shexiang Baoxin Pill" (SBP), a commonly used traditional Chinese medicine, has been used to treat angina, myocardial infarction and coronary heart disease in China for thirty years. SBP has been proven to promote angiogenesis in a rat model of myocardial infarction (MI). The aim of the present study was to determine the pro-angiogenic effects and mechanism of SBP during inflammation or ischemic pathological conditions and elucidate its regulatory effects on endothelial cell function and signaling pathways mediated by macrophages. Methods: We used a polyvinyl alcohol (PVA) sponge implantation mouse model as an inflammatory angiogenesis model and utilized a mouse femoral artery ligation model as a hind limb ischemia model. We also performed cell proliferation, cell migration and tubule formation in vitro experiments to assess the effects of SBP on endothelial cell function and signaling pathways by stimulating macrophage activity. Results: The in vitro experiment results showed that SBP could significantly increase the expression of mRNAs and proteins associated with angiogenesis in endothelial cells by activating macrophages to release pro-angiogenic factors such as Vegf-a. Activation of macrophages by SBP eventually led to endothelial cell proliferation, migration and tubule formation and increased the expression of p-Akt and p-Erk1/2 proteins in the downstream PI3K/Akt and MAPK/Erk1/2 signaling pathways related to angiogenesis, respectively. The in vivo experiment results indicated that SBP had angiogenesis effects in both inflammatory and ischemic angiogenesis models with dose- and time-dependent effects. Conclusion: Shexiang Baoxin Pills can promote angiogenesis by activating macrophages to regulate endothelial cell function and signal transduction pathways. Graphical abstract: Image 1 Highlights: SBP increases expression of mRNAs and proteins in endothelial cells by activating macrophages. SBP leads to endothelial cell proliferation, migration and tubule formation through activation of macrophages. SBP increases expression of the p-Akt and p-Erk1/2 proteins through activation of macrophages. SBP promotes the expression of VEGF-A mRNA, VEGF protein release and microvessel formation in an inflammatory angiogenesis model. SBP promotes neovessel formation and prevents necrosis of acutely ischemic tissues in a hind limb ischemia model.